Wankat and Oreovocz problem-solving strategies in ordinary differential equations teaching materials: A development study - Ariawan, Rezi; Zetriuslita, Zetriuslita (Universitas Maritim Raja Ali Haji, 2024)
Students always experience difficulties in learning ordinary differential equations. The existence of teaching materials that can make students learn actively independently, encourage curiosity, and improve their mathematical abilities is needed. This research aims to produce teaching materials for ordinary differential equations that contain the steps of Wankat and Oreovocz Problem Solving Strategies (I can explore, plan, do it, check, and generalize). This research was conducted in the odd semester of 2023/2024 at the FKIP UIR Mathematics Education Study Program by involving 5th-semester students as product test subjects. Development research was used in this study, using a 4D design (define, design, development, and dissemination). The research instrument consisted of validation sheets and the practicality of teaching materials. Validation of teaching materials was carried out by 3 validators, while the practicality trial of teaching materials was carried out by using teaching materials in the learning process. Data obtained from validators and students will be analyzed descriptively quantitatively, while information related to suggestions, input, and student responses will be analyzed descriptively qualitatively. The teaching materials developed received an assessment with a score of 0.9 or with very valid criteria. While 95% or almost all responses stated that the teaching materials used were very practical, it was still found that students could not learn quickly in completing the tasks.